Grant - Smith, Jean Edward (Simon and Schuster, 2001)
In this comprehensive biography, Jean Edward Smith reconciles these conflicting assessments of Grant's life. He argues convincingly that Grant is greatly underrated as a president. Following the turmoil of Andrew Johnson's administration, Grant guided the nation through the post-Civil War era, overseeing Reconstruction in the South and enforcing the freedoms of new African-American citizens